A NEW ISOLATION OF Bacillus thuringiensis FROM COLOMBIA, TOXIC FOR MOSQUITO LARVES - ORDUZ, SERGIO; CORREA, MARGARITA; MONTOYA, ASTRID ELENA; ROJAS, WILLIAM (Revista Colombiana de Entomología, 1990)
During a survey conducted in Colombia, an isolate of Bacillus thuringiensis showed toxicity towards Culex quinquefaciatus larvae. Parasporal crystals were spherical or irregular in shape and showed a great degree of similarity with those produced by the reference strain B. thuringiensis subsp. israelensis. Supernatant fraction of the whole culture was not toxic. Oxidase, catalase, urease, argynine decarboxylase, amylase, lecithinase, acetil-methil-. carbinol and gelatinase production was positive. Hemolysis on sheep blood agar was "a" type. Production of heat stable B-exotoxin was negative. The isolate CIB-131 showed natural resistance to several antibiotics and was sensible to cephoperazone,cephalotin, nalidixic acid, and trimetoprin sulfamethoxazole.